Eccentric connectivity polynomial of some graph operations - Došlić T.; Ghorbani M.; Hosseinzadeh M.A. (Utilitas Mathematica, 2011)
The eccentricity connectivity polynomial of a graph G is defined as Ξ(G; x) = Σu∈V(G)δG(u)X∈G(u) where ∈G(u) is the eccentricity of the vertex u and δG(U) its degree. In this paper the eccentric connectivity polynomial is computed for several classes of composite graphs.